Answer:
2x+12=24
first you subtract 12 from both sides
2x+12=24
-12. -12
The 12-12 should cancel itself, the rest of the equation you bring down to get
2x=12 (because 24-12=12)
Now you have 2x=12.
you then divide 2x by both sides.
2x=12
/2x=/2x
The 2x/2x cancels itself out so you then solve for 12/2x.
For this you just divide 12/2 which is 6!
x= 6 is your final answer.
to check this equation you can plug your number back into x to see if it is true! 2(6)+12=24.
6 times 2 is 12 and 12+12 is 24 so your answer (6) is true!
hope this helps! :D
Answer:
The second table of values.
Step-by-step explanation:
Let's put the x-values in the second table of values in correct number order:
x: -3, -2, -1, 0, 1
Now, let's write out the y-values in correct number order:
y: 1/4, 1, 4, 16, 64
Finally, let's rewrite the second table of values with the x-values in order and the corresponding y-values underneathe:
x: -3, -2, -1 0 1
y: 64, 16, 4, 1, 1/4
As it can be seen, as the x-values get bigger in value, the y-values get smaller exponentially, which is the definition of exponential decay.
Answer:
2/30
Step-by-step explanation:
2/6 x 1/5
Answer:
8
Step-by-step explanation:
i did 24 divided by 3
hope this helps
-mercury